Level of phosphate diets effect on fibroblast growth factor‐23 levels in chronic kidney disease subjects: A meta‐analysis. Issue 7 (7th April 2021) - Li, Zhong; Hu, Maorong; Guo, Yinxue; Zhang, Lin; Peng, Yunhua; Abdelrahim, Mohamed E. A.; Jiang, Xin
Abstract: Background: High fibroblast growth factor‐23 levels increase cardiovascular disease risk in chronic kidney disease subjects. The effects of dietary phosphate levels on fibroblast growth factor‐23 in chronic kidney disease subjects have conflicting results. This meta‐analysis was performed to evaluate this relationship. Methods: A systematic‐literature search up to July 2020 was performed and 7 studies were detected with 548 chronic kidney disease subjects at the baseline of the studies; a total of 170 of them were with lower dietary phosphate levels and 175 were higher dietary phosphate levels. They reported relationships between dietary phosphate levels and fibroblast growth factor‐23 level in chronic kidney disease subjects. Mean differences (MD) with 95% confidence intervals (CIs) were calculated comparing the lower versus higher phosphate levels effect on urinary phosphate levels and fibroblast growth factor‐23 level in chronic kidney disease subjects using the contentious methods with a random or fixed‐effect model. Results: Lower dietary phosphate levels had significantly lower 24‐hour urinary phosphate excretion (MD, −41.23; 95% CI, −59.95 to 22.52, P < .001), and lower intact fibroblast growth factor‐23 level (MD, −25.68; 95% CI, −39.85 to −11.51, P < .001) compared with higher dietary phosphate levels in chronic kidney disease subjects. However, no significant difference was found between low and high dietary phosphate levels in C‐terminal fibroblast growth factor‐23 level in chronic kidney disease subjects (MD, −7.10; 95% CI, −14.29 to 0.10, P = .05). Conclusions: Lower dietary phosphate levels had significantly lower 24‐hour urinary phosphate excretion, intact fibroblast growth factor‐23 level compared with higher dietary phosphate levels in chronic kidney disease subjects. This relationship forces us to recommend low dietary phosphate levels in chronic kidney disease subjects to decrease fibroblast growth factor‐23 level to avoid any possible cardiovascular disease risk in such a subject.